The Students' Confession toward Common English Classroom Expressions - Hasby, Muhammad; Supraba, Ardhy; Indah, Opik Dwi (Universitas Negeri Gorontalo, 2024)
This research aims to find out the students' confession toward common English classroom expressions. The population of this research is the third-year students of Senior High School 10 Luwu in academic year 2022/2023. The sample of this research is selected through purposive sampling technique. One class represented as the sample that is class XII Exact 1. Questionnaire was used as the instrument of this research. The result of this research shows that the students' confession toward common English classroom expressions gained very positive confession. It revealed most students stated that the material about common English classroom expressions is very effective for the improvement of their English. In other words, most of them confessed that common English classroom expression could improve and develop their English. Finally, the researcher concluded that common English classroom expressions are good material especially for improving the students' English competence.